2022
DOI: 10.1111/opn.12494
|View full text |Cite
|
Sign up to set email alerts
|

Research utilisation in older people care: Translation, cross‐cultural adaptation and validation of instruments into Brazilian Portuguese

Abstract: Aims To translate and culturally validate the Estabrooks' Kinds of Research Utilization (RU) and the Conceptual Research Utilization Scale (CRU) into Brazilian Portuguese; and to describe the research use by health professionals working on Long Term Care Institutions (LTCI) for older people. Background Research utilisation ensures greater quality and effectiveness in the care provided by health professionals. However, there are no instruments to evaluate research utilisation in Latin America countries, like Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The adopted procedures served to guarantee the semantic, idiomatic, conceptual and cultural equivalences, as well as the face of the instrument and the technical terms of access to the professional of the Brazilian version in relation to the original instrument, according to the methodological recommendations proposed by Borsa (2012). Studies of cross-cultural adaptation of instruments have indicated the importance of the equivalence assessment process so that there are no distortions or discrepancies in language, concepts and cultural aspects between the original versions and those produced in the target language (Fares et al, 2023).The analysis phase of the versions of the Marwit-Meuser Caregiver Grief Inventory/Short Form, by the expert judges committee, made it possible to correct inaccuracies in the translations and adjust the wording of the items to the Brazilian cultural context. Also, the suggestions of caregivers, in the assessment phase with the target population, collaborated to obtain the instrument adapted to the Brazilian reality.…”
Section: Discussionmentioning
confidence: 99%
“…The adopted procedures served to guarantee the semantic, idiomatic, conceptual and cultural equivalences, as well as the face of the instrument and the technical terms of access to the professional of the Brazilian version in relation to the original instrument, according to the methodological recommendations proposed by Borsa (2012). Studies of cross-cultural adaptation of instruments have indicated the importance of the equivalence assessment process so that there are no distortions or discrepancies in language, concepts and cultural aspects between the original versions and those produced in the target language (Fares et al, 2023).The analysis phase of the versions of the Marwit-Meuser Caregiver Grief Inventory/Short Form, by the expert judges committee, made it possible to correct inaccuracies in the translations and adjust the wording of the items to the Brazilian cultural context. Also, the suggestions of caregivers, in the assessment phase with the target population, collaborated to obtain the instrument adapted to the Brazilian reality.…”
Section: Discussionmentioning
confidence: 99%